A STUDY ON ANALYSIS OF FINANCIAL DERIVATIVES&SECURITIES - D. Tagore; S. Sudheshna (International Journal of Data Science and IoT Management System, 2026)
This study examines key derivative instruments, including futures, forwards, options, and swaps, and derivative tax analysis their role in reducing financial risk. These instruments help businesses and investors protect themselves from unexpected price changes and market volatility. By using derivatives for hedging purposes, organizations can stabilize earnings and plan operations with greater certainty. Financial derivatives are significant instruments in contemporary financial markets, serving as powerful tools for managing risk, supporting price discovery, and developing effective investment strategies. A derivative is a contract whose value is linked to an underlying asset such as shares, commodities, currencies, interest rates, or market indices. With the rapid expansion of global financial markets, derivatives have gained significant importance in both corporate finance and investment management However, derivative trading also involves challenges such as leverage risk, speculation, and regulatory concerns. Therefore, a balanced understanding of their benefits and limitations is essential for responsible and effective use.